Pharmacological and bioactive properties of Artemisia argyi H. Lév. & Vaniot essential oil: a review - Gao, Qing; Lu, Yanqin (Frontiers in Pharmacology, 2026)
Artemisia argyi H. Lév. & Vaniot Essential Oil (AAEO) is a volatile oil extracted from the leaves and stems of Artemisia argyi. It contains bioactive plant metabolites such as terpenes, aldehydes, ketones, alcohols, and esters. AAEO has antioxidant properties that help remove harmful free radicals and protect cells from damage. It also exerts anti-inflammatory effects by inhibiting the activation of NLRP3 inflammasome (NLR family pyrin domain-containing 3 inflammasome) and the phosphorylation of NF-κB p65, thereby reducing the levels of pro-inflammatory metabolites such as IL-1β, IL-6, and TNF-α. Additionally, AAEO has antimicrobial effects against bacteria, fungi, and viruses. In cancer cell studies, it can slow down the growth and migration of certain cancer cells by inducing apoptosis or inhibiting proliferation. AAEO shows potential in several areas, its insecticidal activity suggests it could be used as a natural mosquito repellent. There are three main challenges with AAEO. First, its chemical composition can vary depending on where it is grown, which affects its stability and effectiveness. Second, most of the evidence for its benefits comes from studies on cells or animals, with few human clinical trials. Third, AAEO has low bioavailability, meaning it is not easily absorbed by the body. Future research should focus on creating unified quality standards for AAEO, conducting large-scale clinical trials to confirm its safety and effectiveness, and developing advanced delivery systems to enhance its absorption and stability.